A new debris sensor based on dual excitation sources for online debris monitoring. (24th July 2015) - Hong, Wei; Wang, Shaoping; Tomovic, Mileta M; Liu, Haokuo; Wang, Xingjian
Abstract: Mechanical systems could be severely damaged by loose debris generated through wear processes between contact surfaces. Hence, debris detection is necessary for effective fault diagnosis, life prediction, and prevention of catastrophic failures. This paper presents a new in-line debris sensor for hydraulic systems based on dual excitation sources. The proposed sensor makes magnetic lines more concentrated while at the same time improving magnetic field uniformity. As a result the sensor has higher sensitivity and improved precision. This paper develops the sensor model, discusses sensor structural features, and introduces a measurement method for debris size identification. Finally, experimental verification is presented indicating that that the sensor can effectively detect 81  μ m (cube) or larger particles in 12 mm outside diameter (OD) organic glass pipe.